(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Arterial stiffness is related with atherosclerosis and cardiovascular disease events. Patients with atherosclerotic disease show to have larger diameters, reduced arterial compliance and lower flow velocities. Aim of study : To compare between patients of two age groups with concomitant diseases diabetes and hypertension in regard to intima media thickness and blood flow characteristics in order to estimate the blood perfusion to the brain via the common and internal carotid arteries. Subject and Methods : 40 patients with (diabetic and hypertension) diseases were enrolled , they were classified according to age. Color Doppler and B mode ultrasound was used to determine lumen Diameter (D), Intima – media thickness (IMT), end diastolic velocity (EDV), peak systolic velocity (PSV), Resistive Index (RI), Pulsatility Index (PI), and the flow rate indices were calibrated and calculated . Results:- Results show that the change in the lumen diameter between the old patients group and the younger group were (2.02%) with insignificant (p value >0.05), and the difference in the in intima-media (IMT) thickness between the two age groups (35- 55) and (56-75) are (33.8%) with significant (p value <0.05). The change difference in peak systolic velocity was (-13.29% ) with insignificant (p value >0.05), while the difference in the (EDV) between both age groups was (-38.02%), with significant p value <0.05. Pressure gradient and flow rate have given insignificant difference between both age groups. Conclusion: The intima media is significantly thicker for the old age group than in the younger group. The increased thickness of intima media did not influence the lumen diameter significantly. A clear change in PSV, EDV, RI, and PI was observed which have influenced blood perfusion to the brain.